Non-Value-Added Activities and Non-Nursing Tasks Affecting Nursing Task Efficiency: A Scoping Review. - Chung, Mi Ha; Kim, Youngah; Kim, Na Yeong; Kim, Min Ju; Kim, Hyeon Jin; Park, Ju Hee; Park, Ji In; Bae, Su Yeon; Bae, Heajin; Lee, Eunjeong; Jeon, Min Young; Choi, Suyoung (Journal of Korean Academy of Nursing Administration, 2025)
Purpose: This study explored the literature on non-value-added (NVA) activities and non-nursing tasks (NNT). We analyzed domestic and international research trends and examined the types and characteristics of nursing tasks to improve efficiency. Methods: A comprehensive literature search was conducted using RISS, DBpia, PubMed, CINAHL, Medline, and Embase. Relevant studies published up to 2024 were identified using keywords such as "non-value-added activity," "non-value-added nursing activity," "non-nursing tasks," and "nursing." Results: Analysis of 25 studies revealed that 11 studies focused on NVA activity and 14 on NNT. Direct nursing tasks were classified into eight categories; indirect tasks were classified into seven categories. NVA activities were grouped into five main categories: "personal," "waste," "documentation," "necessary activities," and "unit-related," with overlapping subcategories such as "interruption" and "duplicating." Similarly, NNT were categorized into eight types, including "admission," "equipment," and "administrative activities." Although conceptually distinct, NVA activities and NNT often overlap. Reducing tasks unrelated to essential nursing care significantly improves job satisfaction, patient outcomes, and work efficiency. These findings provide valuable insights for optimizing nursing workflows and enhancing the quality of care. Conclusion: Identifying and reducing NVA activities and NNT enhance nursing efficiency and provide foundational data for improving clinical practice and patient safety.